2017
DOI: 10.1136/annrheumdis-2016-210478
|View full text |Cite
|
Sign up to set email alerts
|

Knee and hip intra-articular adipose tissues (IAATs) compared with autologous subcutaneous adipose tissue: a specific phenotype for a central player in osteoarthritis

Abstract: IFP but also SPFP and AFP (gathered under the term 'IAAT') may play a deleterious role in OA by affecting joint homeostasis because of their inflammatory phenotype and their close interaction with synovium in the same functional unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 24 publications
10
94
0
1
Order By: Relevance
“…However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue. Importantly, more and more researchers consider the synovial membrane and intra-articular fat pad as an anatomical unit in OA pathogenesis and pain, and inflammation of synovial membrane in the knee joint may play a central role in OA and affect not only cartilage but also intra-articular fat pad [7,29,30]. Moreover, previous team studies have shown that synovial inflammation may affect articular cartilage damage through the innate immune system, aggravating the course of OA [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue. Importantly, more and more researchers consider the synovial membrane and intra-articular fat pad as an anatomical unit in OA pathogenesis and pain, and inflammation of synovial membrane in the knee joint may play a central role in OA and affect not only cartilage but also intra-articular fat pad [7,29,30]. Moreover, previous team studies have shown that synovial inflammation may affect articular cartilage damage through the innate immune system, aggravating the course of OA [11].…”
Section: Discussionmentioning
confidence: 99%
“…Higher level of IL-6 was associated with an increased risk of knee OA progression 64 , and serum levels of IL-6 and TNF-a were associated with joint space narrowing and cartilage loss in older adults 65 . A number of studies reported that IPFP secreted more IL-6 66,67 , IL-8, and prostaglandin E2 than ScAT in patients with knee OA 68 .…”
Section: Mechanisms Underlying the Link Between Adipose Tissue And Knmentioning
confidence: 99%
“…During the past 10 years, IPFP has emerged as a new player in KOA for its pro‐inflammatory nature and ability to regulate cartilage metastasis and synovial inflammation . IPFP has been shown to have different phenotypes than subcutaneous fat tissue, with higher degrees of fibrosis and angiogenesis . The cause of fibrosis has not been elucidated, nor is it known whether cartilage degeneration is associated with IPFP fibrosis.…”
mentioning
confidence: 99%
“…5,6 IPFP has been shown to have different phenotypes than subcutaneous fat tissue, with higher degrees of fibrosis and angiogenesis. 7 The cause of fibrosis has not been elucidated, nor is it known whether cartilage degeneration is associated with IPFP fibrosis.…”
mentioning
confidence: 99%